Faktor Risiko Kejadian Anemia pada Ibu Hamil di Rumah Sakit BARI Palembang - Siti Amallia; Rahmalia Afriyani; Siska Putri Utami (Politeknik Kesehatan Tanjung Karang, 2017)
The appearance of anemia during the maternity caused the death of mothers indirectly. Based on the data from BARI hospital Palembang in 2015, it was found for about 29 (13 %) of 2218 maternity mothers affected by anemia. The objectives of this study were to discover the influential factors on the appearance of anemia on maternity women in the BARI Hospital Palembang in 2015. The cross-sectional approach was applied in this study. The population of the study was all the maternity women who checked their pregnancy in the BARI hospital in 2015. There were 236 respondents taken by using simple random sampling. Data were analyzed by using frequency analysis, chi-square analysis, and logistic regression analysis. The result of study showed that 31 (13.1%) respondents got anemia during their pregnancy, there was the correlation between the age (p-value=0.032) and parity of maternity women (p-value=0.005) on anemia, and there was no correlation between the education and occupation of maternity women who affected by anemia. The regression logistic test showed that age and parity influenced the affection of anemia on maternity women and the most influential factor was the parity with OR = 4.012. Suggested to health officer will improve the counseling for maternity women about the importance of family planning after childbirth and control the number of children, so anemia cases in pregnancy will be decreased.